التراث الإسلامي وعلاقته بالثقافة الإسلامية دراسة وصفية تحليلة (Al Basirah, 2020)
This research clarifies the concept of Islamic Heritage, its importance,benefits, divisions, and the West's position towards this original heritage, andhow it is considered one of the most important components of the generalIslamic culture. This heritage that we inherited from the forefathers isconsidered one of the most important sources of Islamic culture that relied ondrawing its characteristics on the original sources of Islam, and with thisspecificity the Islamic culture was distinguished similarly like Islamiclegislations and unlike the other man- made laws that are subject to deficiency,ruin , destruction and ending, the Islamic culture was based in its sources onthe Holy Qur'an and the noble Prophet's Sunnah, therefore, its characteristicswere consistent with the characteristics of Islam because of its closeconnection with it in terms of source, strength, taking , survival , continuityand empowerment, and because it carries its approach, goals and objectives inwhich the Islamic culture absorbs all different aspects of life from foreignpolicy, internal governance, judiciary, administration, economics, socialaspects, transactions and worship, and many other diverse areas in people'sindividual or social lives, thus, it is surrounded by man in different stages ofhis life from birth, childhood and manhood, and in his relationships needsinternally and externally and all of these can be discussed in terms ofauthenticity of Islamic Heritage, because it is considered one of the mostimportant topics that the Islamic culture taken care of by research and studythrough the sources, bases, characteristics, goals and effects on individual andsociety and directs it in all matters of life.
Keywords: Islamic heritage, Islamic culture, man - made laws, objectives, characteristics.